Wheat resistance to blast using a non-host selective toxin and host metabolic reprogramming through a successful infection by Pyricularia oryzae - Aucique Pérez, Carlos Eduardo (2016)
Blast, caused by Pyricularia oryzae, has become an economically important disease in wheat in South America. One of the management strategies for minimizing the losses caused by blast includes the use of resistant cultivars. Alternatively, the use of inducers of resistance showed the potentiation to increase wheat resistance to blast. This study aimed: i) to determine the physiological and biochemical alterations in wheat plants sprayed with a non-phytotoxic concentration of α-picolinic acid (PA), which is a non-host selective toxin produced by P. oryzae and ii) to establish the degree of metabolic manipulation exerted during the infection by P. oryzae on plants from cultivars with different levels of basal resistance to blast. The spray of leaves of plants with a non-phytotoxic concentration of PA (0.1 mg mL -1 ) resulted in less blast symptoms in association with a better photosynthetic performance, an improvement on the antioxidant metabolism and reduced concentrations of H 2 O 2 , O 2 ●- and malondialdehyde. The cultivars BR-18 and EMBRAPA-16 were more resistant to blast in comparison to cultivar BRS-Guamirim. The photosynthetic performance of the infected plants was altered due to diffusional and biochemical limitations for CO 2 fixation. During the asymptomatic phase of P. oryzae infection, drastic changes in the carbohydrates metabolism and on the levels of amino acids, intermediates compounds of Krebs cycle and polyamines occurred on plants from the three cultivars suggesting a metabolic manipulation exerted by the pathogen. However, amore efficient antioxidant metabolism was able to help the wheat plants to counteract against the deleterious effects of P. oryzae infection in association with great phenylalanine ammonia lyases and polyphenoloxidases activities and high concentrations of phenolics and lignin. Based on this information, it is possible to conclude that a non- phytotoxic concentration of PA elicited the activation of host defense mechanisms that reduced blast severity. Likewise, the infection of leaves by P. oryzae induced remarkable disturbances in the primary metabolism and some of them were conserved among the cultivars regardless of their basal level of resistance to blast.